Meningkatkan Kemampuan Mengenal Nama-Nama Hewan Melalui Media Busy Book Bagi Murid Disabilitas Rungu - Rahmi Aulia; Zulmiyetri Zulmiyetri; Rahmahtrisilvia; Mardhatillah Zulpiani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The ability to recognize animal names is part of vocabulary mastery which is still a challenge for some deaf students due to limitations in receiving verbal information, so more concrete and visual learning media are needed. This study aims to analyze the effectiveness of busy book learning media in improving the ability to recognize animal names around the house in one fourth-grade student with mild hearing impairment at SLB Negeri 1 Harau. The study used an experimental method with a Single Subject Research (SSR) design type A-B-A. Data were collected through observation, tests, documentation, and interviews, then analyzed using visual graphic analysis which included analysis within conditions and analysis between conditions. The results showed an increase in the ability to recognize animal names from 20% in the baseline condition (A1) to 100% in the intervention phase (B), and this ability remained in the second baseline phase (A2). These findings indicate that the use of busy book media can improve the ability to recognize animal names through the presentation of material that is concrete, visual, and interactive. Thus, busy book media can be used as an alternative learning method to support the vocabulary development of deaf students.